Palms - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Non-wood forest products: tropical palms. By D V Johnson. 1997. 166 pp. Distribution and Sales Section, Food and Agriculture Organization Viale delle Terme di Caracalla 00100 Rome Italy